Acute Pancreatitis Mimicking Perforation After Nonampullary Duodenal Polypectomy - Onwuzo, Chidera; Nasr, Dayana; Jaffar, Huda; Alvina, FNU; Peleg, Noam (Brazilian Journal of Case Reports, 2026)
Post-procedural pancreatitis after non-ampullary duodenal resection is uncommon. We describe a 73-year-old man with gastroesophageal reflux disease who underwent esophagogastroduodenoscopy (EGD) for left upper-quadrant pain at an outside facility where a 1-cm sessile polyp in the second portion of the duodenum, biopsy-proven adenoma, was removed piecemeal with hot snare using a side-viewing endoscope. Two hours later, he developed severe epigastric pain and presented the next day with leukocytosis and lipase 9,000 U/L. Computed tomography (CT) showed diffuse mesenteric and omental edema, especially in the anterior pararenal space, suggestive of acute pancreatitis. Given the recent duodenal resection and severity of pain, duodenal perforation was clinically suspected, prompting transfer. On arrival, repeat cross-sectional imaging reviewed with surgery showed procedure-related acute pancreatitis with pancreaticoduodenal groove edema, likely secondary to recent polypectomy, no perforation, and conservative management was continued. He improved with support and was discharged on day 7.